A Hydrogel Platform that Incorporates Laminin Isoforms for Efficient Presentation of Growth Factors – Neural Growth and Osteogenesis. (21st March 2021) - Dobre, Oana; Oliva, Mariana A. G.; Ciccone, Giuseppe; Trujillo, Sara; Rodrigo‐Navarro, Aleixandre; Venters, Douglas Cormac; Llopis‐Hernandez, Virginia; Vassalli, Massimo; Gonzalez‐Garcia, Cristina; Dalby, Matthew J.; Salmeron‐Sanchez, Manuel
Abstract: Laminins (LMs) are important structural proteins of the extracellular matrix (ECM). The abundance of every LM isoform is tissue‐dependent, suggesting that LM has tissue‐specific roles. LM binds growth factors (GFs), which are powerful cytokines widely used in tissue engineering due to their ability to control stem cell differentiation. Currently, the most commonly used ECM mimetic material in vitro is Matrigel, a matrix of undefined composition containing LM and various GFs, but subjected to batch variability and lacking control of physicochemical properties. Inspired by Matrigel, a new and completely defined hydrogel platform based on hybrid LM‐poly(ethylene glycol) (PEG) hydrogels with controllable stiffness (1–25 kPa) and degradability is proposed. Different LM isoforms are used to bind and efficiently display GFs (here, bone morphogenetic protein (BMP‐2) and beta‐nerve growth factor (β‐NGF)), enabling their solid‐phase presentation at ultralow doses to specifically target a range of tissues. The potential of this platform to trigger stem cell differentiation toward osteogenic lineages and stimulate neural cells growth in 3D, is demonstrated. These hydrogels enable 3D, synthetic, defined composition, and reproducible cell culture microenvironments reflecting the complexity of the native ECM, where GFs in combination with LM isoforms yield the full diversity of cellular processes. Abstract : A hydrogel platform based on full‐length laminin isoforms that target specific tissues for 3D in vitro tissue models is presented. The system allows controlled mechanical properties, degradability, and importantly, uses the affinity of laminins for growth factors. This platform enables osteogenesis using BMP2 and neural processes using NGF.